2022
DOI: 10.1007/s10802-022-00957-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood executive functions and ADHD symptoms predict psychopathology symptoms in emerging adults with and without ADHD: a 10-year longitudinal study

Abstract: Deficits in executive functions (EFs) are theorized to play an important role in causing functional impairment and associated psychopathology in individuals with ADHD. The objective of this study was to examine the role of EFs and ADHD symptoms as longitudinal predictors of psychopathology symptoms in individuals with ADHD and typically developing individuals. We assessed individuals with and without ADHD (N = 135) with neuropsychological tests of EFs and scales of ADHD symptoms and psychopathology symptoms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Thus, it is interesting that EF, as measured with neuropsychological tests, did not predict QoL or functional impairments in this study. We have previously found, in the same sample, that neuropsychological tests of EF at baseline predicted psychopathology symptoms, including internalizing difficulties, at the 10-year follow-up (Orm, Andersen, et al, 2022). Thus, there is a possibility that EF affects QoL and functional impairments indirectly via its effect on internalizing difficulties, which are related to lower QoL and functional impairments (Haugan et al, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Thus, it is interesting that EF, as measured with neuropsychological tests, did not predict QoL or functional impairments in this study. We have previously found, in the same sample, that neuropsychological tests of EF at baseline predicted psychopathology symptoms, including internalizing difficulties, at the 10-year follow-up (Orm, Andersen, et al, 2022). Thus, there is a possibility that EF affects QoL and functional impairments indirectly via its effect on internalizing difficulties, which are related to lower QoL and functional impairments (Haugan et al, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…For EF, we computed a composite score based on the four neuropsychological tests. This composite score was computed following the procedure described by Orm et al (2022). We converted test raw scores into Z -scores and then added the Z -scores into a composite score where higher scores indicate more EF deficits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brocki et al (2010) and Bohlin et al (2012) studies showed that executive function at age 5 significantly predicts ADHD symptoms at age 7 (Fan & Wang, 2022). In addition, recent studies have shown that childhood executive functions are predictive later psychopathological symptoms in adolescents and emerging adults with ADHD (Meza et al, 2021; Miller et al, 2012; Orm et al, 2022; Owens & Hinshaw, 2016). Most children and adolescents with ADHD suffer from impairments in executive functions, particularly in the field of behavior inhibition, self-regulation, and selective attention, and the apparent symptoms of this disorder are due to deficiency in these three components (Crisci et al, 2021; Fay-Stammbach et al, 2014; Willcutt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%